Relationship Between Student Perception on Use Animation Film Media and Learning Motivation with Student Islamic Religious Education Learning Outcomes In MTsN Setu Bekasi District - Rahmawati, Junia; Alam, Dede Rubai Misbahul; Khoir, Abdul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Learning outcomes are one indicator of successful learning or not. This study aims to determine the relationship between students' perceptions of using animated film media and learning motivation both partially and jointly with Islamic education learning outcomes of MTSn students in the Setu Bekasi district. The research method uses a correlational approach. Data analysis using the T-test and ANOVA test. The sample used was 180 students from a population of 225 students taken from grade 7 at MTSn, Setu district, Bekasi. The results of this study indicate that the research hypothesis is proven to have a Py12 value > 0 which explains that there is a positive relationship between student's perceptions of the use of animated film media (X1) and learning motivation (X2) together with PAI learning outcomes of students (Y) MTSn Setu sub-district Bekasi. In addition to testing, animated film media and learning motivation partially correlate with learning outcomes.